Literatura e cinema: escrita literária e escrita fílmica - Martirani, André Alves (2012)
This dissertation proposes a study of the text, The Concept Zero, an international plot for the independence of Amazonia, by A. J. Barros, with the purpose of determining whether the literary work has elements that would allow its adaptation to the cinema, in other words, qualities favorable for an audiovisual transposition. The structure of the work characters, space, time, action, point of view, narrative resources and dramatic curve, among other elements will be studied from a literary theory and film writing approach. Based on the analysis of the work, aspects which allow a dialogue between codes will be identified. Analysis of the data obtained allows identification of points favorable for adaptation to cinematographic language, as well as more accurate identification of points that are not suitable for this purpose. Following the analysis, we formally indicate ideas to guide the cinematographic script and prepare part of the script itself, transposing a portion of the work that extends from its start to the end of Book I The River of Doubt into film writing. Finally, we offer a brief commentary on the process for adapting the novel